2009
DOI: 10.1007/s11547-009-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty: optimizing the procedure after treatment of 250 vertebral levels under fluoroscopic guidance

Abstract: PVP is a safe, rapid, effective and costeffective therapy for VCFs, requiring only brief hospital admission and with long-lasting clinical results, when performed under good-quality radiological guidance, when correct indications are respected and when it is associated with rehabilitation therapy in the follow-up. It is a valid alternative to conservative therapy, which is burdened by high healthcare costs and often requires long-term immobilisation of frail and elderly patients at risk of clinical complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Our study demonstrated PVP is an effective procedure to rapidly reduce back pain in patients affected by acute OVCFs assessed by MRI (61,62). We confirmed in our sample, femoral bone density impacts more deeply than vertebral T-score and/or BMD on bone strenght, as it is less affected by any interferences (52).…”
Section: Resultssupporting
confidence: 75%
“…Our study demonstrated PVP is an effective procedure to rapidly reduce back pain in patients affected by acute OVCFs assessed by MRI (61,62). We confirmed in our sample, femoral bone density impacts more deeply than vertebral T-score and/or BMD on bone strenght, as it is less affected by any interferences (52).…”
Section: Resultssupporting
confidence: 75%
“…The papers retrieved focused on surgery rather than rehabilitation. However, Pedicelli et al [21] described the importance of postoperative rehabilitation to maximise the outcome in their sample after VP. Even though a detailed description of the rehabilitative pathway was lacking, these authors dealt with the subject to some degree and reported on the physical therapies used as postoperative tools (laser, magnetic fields).…”
Section: Discussionmentioning
confidence: 99%